The Influence of Airpower upon History : Statesmanship, Diplomacy, and Foreign Policy since 1903 - Parillo, Mark P., 1955-; Higham, Robin, 1925-2015 (Book collections on Project MUSE., 2013)
From early zeppelins, to the Luftwaffe and the Enola Gay, to the unmanned aerial vehicles of today, air power has long been regarded as an invaluable instrument of war. However, nations have employed aircraft for many other purposes as well; they provide security and surveillance, and they are vital to myriad diplomatic and humanitarian efforts. Air power has become a means for statesmen to advance a variety of goals, opening up new possibilities and problems in times of peace as well as war. The Influence of Air Power upon History examines the many ways in which aviation technology h.